Temporality a NVRAM-based Virtualization Platform - Sartakov, Vasily A.; Martens, Arthur; Kapitza, Rüdiger (Proceedings of the IEEE Symposium on Reliable Distributed Systems, 2016)
Power failures in data centers and Cloud Computing infrastructures can cause loss of data and impact revenue. Existing best practice such as persistent logging and checkpointing add overhead during operation and increase recovery time. Other solutions like the use of an uninterruptable power supply incur additional costs and are maintenance-intensive. Novel persistent main memory, i.e. memory that retains stored data without an external source of power, firstly prevents data loss in case of a power outage, secondly reduces the time for a system reboot and thirdly enables to continue operation at full-speed after a recovery. Yet new architectures and programming models are required to utilize persistent main memory. We present Temporality a virtualization layer that runs virtual machines in persistent memory and offers virtual persistent memory. It can be used as a basis for future Cloud platforms to allow applications the utilization of persistent memory without any changes. It provides safety of volatile data, significantly decreases overall recovery time and prevents subsequent performance degradation.
CRIS-Team Scopus Importer:2022-07-19
Keywords: Cloud Computing; NVRAM; Virtualization